2009
DOI: 10.1017/s1047951109003977
|View full text |Cite
|
Sign up to set email alerts
|

The impact of oral health on the quality of life of young patients with congenital cardiac disease

Abstract: The purposes of our study were, first, to determine the prevalence of dental caries in young patients with congenital cardiac disease, second, to determine the effect of oral health in their quality of life, third, to examine parental knowledge about associations between oral health and cardiac health, and fourth, to examine parental perceptions regarding access to dental care. A standardized questionnaire was given to a convenience sample of parents of 43 children with cardiac disease and 43 healthy controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
4
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 24 publications
5
62
4
1
Order By: Relevance
“…Another recent study reported a low caries index and no statistical difference when comparing young congenital heart disease patients with healthy controls. 6 The data from this study group showed that the test group had a reduced oral health-related quality of life in some specific domains, including family stress and psychological impact on the child. 6 Current evidence from animal models suggests that bacteremia leading to infective endocarditis may be induced by routine situations, such as oral hygiene and chewing.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…Another recent study reported a low caries index and no statistical difference when comparing young congenital heart disease patients with healthy controls. 6 The data from this study group showed that the test group had a reduced oral health-related quality of life in some specific domains, including family stress and psychological impact on the child. 6 Current evidence from animal models suggests that bacteremia leading to infective endocarditis may be induced by routine situations, such as oral hygiene and chewing.…”
Section: Introductionmentioning
confidence: 75%
“…Fonseca et al concluded that the most significant barrier to good oral health is often the lack of knowledge. 6 The population comprising our study was essentially a surgical group, reflecting our hospital's profile (tertiary care, reference cardiology hospital). This aspect could also have contributed to the process of caries development, since the complexity of the underlying cardiac disease may lead parents to underestimate the importance of oral hygiene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study, which focused mainly on the quality of life of children with heart disease, observed that parents of special care children felt more guilty than parents of healthy children. 20 This relationship between parental guilt and oral problems could be due to the impact that ECC has on the child, the family and the community. 21 "Guilt" is a feeling that occurs when one assesses one's specific action as a failure or, especially, when the particular action has led to failure.…”
Section: Discussionmentioning
confidence: 99%